Safety Assessment of Cassava Pulp-Derived Dietary Fiber: Acute and Sub-Acute Toxicity Evaluation - Naiyana Nontamart; Kakanang Posridee; Parin Suwannaprapha; Rungrudee Srisawat; Ratchadaporn Oonsivilai (Toxics)
This study rigorously evaluated the safety profile of dietary fiber extracted from cassava pulp, a promising functional food ingredient, through acute and 28-day sub-acute oral toxicity assessments in Wistar rats. This research hypothesized that cassava pulp fiber would exhibit minimal toxicity across a range of doses. In the acute study, rats received single oral doses of 175, 550, or 2000 mg/kg, while the sub-acute toxicity study involved daily doses of 250, 500, or 1000 mg/kg, with satellite groups included for reversibility assessment. Comprehensive monitoring encompassed clinical signs, mortality, body weight, food intake, hematological and biochemical parameters, relative organ weights, and detailed histopathological examination. Remarkably, no treatment-related mortality or overt clinical signs of toxicity were observed in either study. The LD50 was higher than 2000 mg/kg for the acute study and the no-observed-adverse-effect level (NOAEL) was determined to be 2000 mg/kg for the acute study and 1000 mg/kg for the sub-acute toxicity study, indicating a high margin of safety. While statistically significant alterations were noted in some hematological, biochemical, and relative organ weight parameters, these changes were not considered toxicologically relevant. Notably, histopathological changes in the lungs were observed across all groups, including controls, warranting further investigation. These findings suggest that cassava pulp fiber is well tolerated at high oral doses, supporting its potential for safe application in food and nutraceutical formulations. However, the observed lung alterations necessitate further research to elucidate their etiology and clinical significance.